Graphitic carbon nitride (g-C3N4) coated titanium oxide nanotube arrays with enhanced photo-electrochemical performance. Issue 32 (22nd July 2016) - Sun, Mingxuan; Fang, Yalin; Kong, Yuanyuan; Sun, Shanfu; Yu, Zhishui; Umar, Ahmad
Abstract : In situ growth of g-C3 N4 on the surface of TiO2 nanotube arrays (g-C3 N4 /TiO2 ) was achieved via the vapor-pyrolysis of melamine and a better photo-electrochemical performance was demonstrated. Abstract : Herein, we report the successful formation of graphitic carbon nitride coated titanium oxide nanotube array thin films (g-C3 N4 /TiO2 ) via the facile thermal treatment of anodized Ti sheets over melamine. The proportion of C3 N4 and TiO2 in the composite can be adjusted by changing the initial addition mass of melamine. The as-prepared samples are characterized by several techniques in order to understand the morphological, structural, compositional and optical properties. UV-vis absorption studies exhibit a remarkable red shift for the g-C3 N4 /TiO2 thin films as compared to the pristine TiO2 nanotubes. Importantly, the prepared composites exhibit an enhanced photocurrent and photo-potential under both UV-vis and visible light irradiation. Moreover, the observed maximum photo-conversion efficiency of the prepared composites is 1.59 times higher than that of the pristine TiO2 nanotubes. The optical and electrochemical impedance spectra analysis reveals that the better photo-electrochemical performance of the g-C3 N4 /TiO2 nanotubes is mainly due to the wider light absorption and reduced impedance compared to the bare TiO2 nanotube electrode. The presented work demonstrates a facile and simple method to fabricate g-C3 N4 /TiO2 nanotubes and clearly revealed that the introduction of g-C3 N4 is a new and innovative approach to improve the photocurrent and photo-potential efficiencies of TiO2 .